Mergers and Acquisitions Versus Greenfield Investment, Absorptive Capacity, and Economic Growth: Evidence from 12 New Member States of the European Union - Eren, Tevfik Mesut; Zhuang, Hong (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2015)
Using disaggregated FDI data on 12 new member states of the European Union from 1999 to 2010, this paper examines whether different types of FDI have differential effects on economic growth. Our results show that mergers and acquisitions (M&As) and greenfield investment do not on their own have significant growth effects in these economies. In both cases, the availability of absorptive capacity plays an important role in stimulating their growth effects. Moreover, a developed financial system complements the impact of M& As on economic growth, while a minimum threshold level of human capital needs to be reached so that greenfield investment is beneficial for economic growth. Domestic investment is revealed to be a consistent contributor to economic growth.
Keywords: Central and Eastern Europe; Economic growth; European Union New Member States; Foreign direct investment; Greenfield investment; Mergers and acquisitions; Foreign direct-investment; Transition economies; Countries; Fdi; Eastern; Sector; Impact; Export